INSTRUCTORS’ MOTIVATION AS CORRELATES OF SUPERIORS’ TRANSFORMATIONAL LEADERSHIP STYLES IN AN INSTITUTE OF TECHNOLOGY IN SHANDONG, CHINA - 刘, 志菁 (Pacific International Journal, 2023)
This study aims to determine the relationship between transformational leadership styles of department heads and instructors’ motivation at Shandong Huayu Institute of Technology in China. A descriptive comparative-correlational design will be utilized. The Multifactor Leadership Questionnaire and a motivation scale will be administered to 294 instructors to assess transformational leadership styles (idealized influence, inspirational motivation, intellectual stimulation, individual consideration) and types of motivation (power, achievement, affiliation, competence). Quantitative data will be analyzed using descriptive and inferential statistics. Results will determine if there are significant relationships between leadership styles and motivation, which can inform leadership training programs. This addresses a gap in understanding transformational leadership and instructor motivation in the Chinese higher education context.